Global and regional brain hypometabolism on FDG-PET in treated HIV-infected individuals. (23rd October 2018) - Hammoud, Dima A.; Sinharay, Sanhita; Steinbach, Sally; Wakim, Paul G.; Geannopoulos, Katrina; Traino, Katherine; Dey, Amit K.; Tramont, Edmund; Rapoport, Stanley I.; Snow, Joseph; Mehta, Nehal N.; Smith, Bryan R.; et al.
Abstract : Objective: To quantitatively measure brain glucose metabolism in treated HIV-positive individuals with [ 18 F]-labeled fluorodeoxyglucose (FDG) PET/CT. Methods: We performed a cross-sectional comparison of FDG uptake in 47 treated HIV+ individuals, 10 age-matched controls (HIV−) sharing many of the comorbid conditions seen in the HIV+ group, and 19 age-matched healthy controls (HCs). We compared whole-brain (WB) and regional FDG standardized uptake values (SUVs) of select subcortical/central structures among the groups and correlated the values to clinical and neuropsychological assessments. A variable selection model was used to predict SUVs in HIV+ (n = 47) and in combined HIV+ and HIV− participants (n = 57). Results: We found lower WB SUVmax in HIV+ participants compared to HCs but not to HIV− participants. Among the relative SUVmean measurements (regional SUVmean/WB SUVmean), only relative thalamic uptake values were lower in HIV+ compared to HIV− participants. When HIV+ and HIV− participants were grouped, cardiovascular disease risk scores best predicted WB SUVmean and SUVmax, while HIV status best predicted thalamic relative SUVmean. Conclusions: We identified an important role for cardiovascular disease in neuronal loss/dysfunction, as measured by FDG-PET, in treated HIV+ patients. This underscores the need for shifting the focus of clinical intervention in this vulnerable population from HIV effects alone to a wider set of comorbid conditions, mainly cardiovascular disease. Only the thalamus showed significantly lower relative uptake in the HIV+ compared to the HC and HIV− groups. This needs to be further evaluated for underlying pathophysiology and potential association with memory, executive functioning, and attention deficits seen in the HIV+ population.